A EUropean study on effectiveness and sustainability of current Cardiac Rehabilitation programmes in the Elderly: Design of the EU-CaRE randomised controlled trial. (29th August 2020) - Prescott, Eva; Meindersma, Esther P; van der Velde, Astrid E; Gonzalez-Juanatey, Jose R; Iliou, Marie Christine; Ardissino, Diego; Zoccai, Giuseppe Biondi; Zeymer, Uwe; Prins, Leonie F; Van't Hof, Arnoud WJ; Wilhelm, Matthias; de Kluiver, Ed P
Abstract: Background: Cardiac rehabilitation (CR) is an evidence-based intervention to increase survival and quality of life. Yet studies consistently show that elderly patients are less frequently referred to CR, show less uptake and more often drop out of CR programmes. Design: The European study on effectiveness and sustainability of current cardiac rehabilitation programmes in the elderly (EU-CaRE) project consists of an observational study and an open prospective, investigator-initiated multicentre randomised controlled trial (RCT) involving mobile telemonitoring guided CR ( m CR). Objective: The aim of EU-CaRE is to map the efficiency of current CR of the elderly in Europe, and to investigate whether m CR is an effective alternative in terms of efficacy, adherence and sustainability. Methods and results: The EU-CaRE study includes patients aged 65 years or older with ischaemic heart disease or who have undergone heart valve surgery. A total of 1760 patients participating in existing CR programmes in eight regions of Europe will be included. Of patients declining regular CR, 238 will be included in the RCT and randomised in two study arms. The experimental group ( m CR) will receive a personalised home-based programme while the control group will receive no advice or coaching throughout the study period. Outcomes will be assessed after the end of CR and at 12 months follow-up. The primary outcome is VO2peak and secondary outcomes include variables describing CR uptake, adherence, efficacy and sustainability. Conclusion: The study will provide important information to improve CR in the elderly. The EU-CaRE RCT is the first European multicentre study of m CR as an alternative for elderly patients not attending usual CR.